Feminine and masculine style as a spirit of contemporary ‘Batik’ textile making in Semarang - Sugiarto, Eko; Syarif, Muhammad Ibnan; Nashiroh, Putri Khoirin; Maulana, Anand Luthfi (Research Journal in Advanced Humanities, 2023)
The creation of batik Semarang motifs has been limited to visualizing regional icons, even though batik cloth in Semarang has a very good position and potential to be developed in a contemporary direction. On the other hand, the feminine and masculine patterned designs also underlie this development. This study aims to reconstruct batik Semarang designs with contemporary feminine and masculine clothing styles. This study used art practice-based research methods to produce and present batik motifs. The research stages included (a) art data collection, (b) presentation of ideas, (c) artistic action, and (d) presentation of works. This study has resulted in the development of contemporary Semarang batik motifs. The source of the idea of ​​motifs comes from the natural-physical and socio-cultural environment in Semarang, which is visualized by stylization. The main motif designed does not use repetitive patterns of batik motifs, while filler and supporting motifs (isen-isen) are designed using repetitive patterns. The color identity of the textile is illustrated based on the character of femininity and masculinity.